Analisis Dinamika Penetapan UMK: Peran Ekonomi dan Sosial di Sumatera Selatan Periode 2020 – 2024 - Haidar Akhmad Al Barabasi; Hastarini Dwi Atmanti (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study analyzes the dynamics of minimum wage determination (UMK) in South Sumatra from 2020 to 2024, emphasizing the role of economic and social indicators. Utilizing panel data regression with the Fixed Effect Model (FEM), the study investigates the influence of open unemployment rate, Human Development Index (HDI), labor force participation rate, Gross Regional Domestic Product (GRDP), and poverty rate on the determination of district/city minimum wages. The findings reveal that HDI has a positive and significant effect on UMK, indicating that improved human development supports higher wage standards. Conversely, the open unemployment rate and poverty rate negatively and significantly affect UMK, suggesting that socioeconomic vulnerabilities limit local governments' capacity to increase wages. Meanwhile, labor force participation and GRDP are not statistically significant. These results underscore the complexity of wage policy formulation, which must balance worker welfare and economic resilience at the regional level. The study offers relevant policy implications for equitable wage setting through human capital development and poverty reduction strategies.